2016
DOI: 10.1155/2016/9894054
|View full text |Cite
|
Sign up to set email alerts
|

Method to Reduce the False-Positive Rate of Loss of Resistance in the Cervical Epidural Region

Abstract: Background. The cervical epidural space can be detected by the loss of resistance (LOR) technique which is commonly performed using air. However, this technique using air has been associated with a high false-positive LOR rate during cervical interlaminar epidural steroid injections (CIESIs). Objective. We investigated whether the detection of LOR with contrast medium might reduce the false-positive LOR rate on the first attempt. Methods. We obtained data retrospectively. A total of 79 patients were divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
1
10
1
Order By: Relevance
“…This study demonstrated the incidence of false LOR as 29.5% which is similar to previous results performed in cervical area, [ 1 , 5 ] and higher than the results of lumbar area. [ 1 ]…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This study demonstrated the incidence of false LOR as 29.5% which is similar to previous results performed in cervical area, [ 1 , 5 ] and higher than the results of lumbar area. [ 1 ]…”
Section: Discussionsupporting
confidence: 90%
“…To reduce the false LOR, various methods including the use of contrast medium or epidrum to detect LOR have been studied. [ 5 , 6 ] We suggest that EPWA might be more valuable if it is applied to CESI which shows high false LOR rate and one adjunctive method to reduce the failure of CESI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The paramidline approach is preferred when a midline approach is difficult, as in cases with ossification of the supraspinous ligament or Baastrup disease. The loss of resistance as the needle traverses the ligamentum flavum, which indicates that the needle is in the epidural space, can be unreliable, compared with use of test injections of contrast material (55,(63)(64)(65). A test injection of contrast material would result in a vertical semilunar-shaped contrast agent deposit along the spinolaminar line on the lateral view and a thick ipsilateral contrast agent shadow along the medial margin of the upper and lower pedicles and the exciting nerve sheath on the AP view (Fig 6a-6c).…”
Section: Lumbar Interlaminar Injectionmentioning
confidence: 99%